2015
DOI: 10.1161/circep.114.001827
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ripple Mapping to Visualize Slow Conduction Channels Within the Infarct-Related Left Ventricular Scar

Abstract: Background-Ripple mapping (RM) displays each electrogram at its 3-dimensional coordinate as a bar changing in length according to its voltage-time relationship with a fiduciary reference. We applied RM to left ventricular ischemic scar for evidence of slow-conducting channels that may act as ventricular tachycardia (VT) substrate. Methods and Results-CARTO-3© (Biosense Webster Inc, Diamond Bar, CA) maps in patient undergoing VT ablation were analyzed on an offline MatLab RM system. Scar was assessed for sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 22 publications
4
43
0
Order By: Relevance
“…Previously, in a retrospective series, we were able to show that sites of entrainment with concealed fusion, excellent pace maps, and termination colocated to such RMCCs. 9 In the current study, we were able to show that where the VT RMDP could be mapped, it was contained entirely within an RMCC, though this was limited to only 3 cases. In certain areas, it was formed by functional block within the RMCC borders.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Previously, in a retrospective series, we were able to show that sites of entrainment with concealed fusion, excellent pace maps, and termination colocated to such RMCCs. 9 In the current study, we were able to show that where the VT RMDP could be mapped, it was contained entirely within an RMCC, though this was limited to only 3 cases. In certain areas, it was formed by functional block within the RMCC borders.…”
Section: Discussionmentioning
confidence: 52%
“…8 We have previously described how RM is able to visualize conducting channels of electrogram activation within scar using an offline system in a retrospective series of ventricular substrate maps. 9 This showed that pacing sites with good pace maps and where entrainment mapping confirmed participation in VT colocated with the identified ripple mapping conducting channels (RMCCs). On the basis of these studies, we propose to test the hypothesis that ablating RMCCs within the postinfarct scar can prevent VT recurrence.…”
mentioning
confidence: 91%
“…19 Jamil-Copley et al more recently showed the potential utility of ripple mapping which demonstrates both voltage and propagation channels into scar in a single dynamic display. 20 This technology has the advantage of displaying complex or continuous fractionated local electrograms as time-dependent propagation, rather than choosing a single annotation for timing.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple points are displayed, with the timing of each point being relative to a fiducial reference signal. 7,8 This is then presented as a movie to allow visualization of the activation wavefront direction. By superimposing the bars on a display of bipolar voltage amplitude, RM is unique in presenting both voltage as well as activation information on the same shell ( Figure 1 and Movie I in the Data Supplement).…”
mentioning
confidence: 99%